Exploring the impact of women’s empowerment on health and nutritional status of children and women in India - Sindhuja, Naga; Venkata, Padigapati (Indian Council of Agricultural Research, 2023)
The focus on gender equality and women’s empowerment are crucial in nurturing health and human development. Using unit-level data from NFHS5 (Demographic and Health Survey data), we developed a women’s empowerment index for India and assessed its impact on children’s (0–59 months) and women’s (15–49 years) health and nutritional outcomes. Principle component analysis was used to develop a survey-based women empowerment index (SWPER) based on six domains: domestic violence, decisionmaking, social independence, economic independence, access to health care, and age at critical life events. The internal reliability of the index was confirmed by a Cronbach alpha value of 0.64. Bivariate analysis indicated that nearly one-third of women in India were highly empowered, with urban women (50.66%) having an edge compared to their rural counterparts (24.45%). Women’s empowerment varied with their family wealth status and their state of residence. Logistic regression analysis was used to investigate the relationship between selected health and nutritional outcomes and women’s empowerment. The results suggested that women’s empowerment could significantly reduce children’s stunting, wasting and underweight status; and anemia in women. The SWPER for India developed in this study could be used to compare the status of women’s empowerment with other countries for which it is already available. Further, our findings highlight the importance of framing and implementing suitable policies and interventions to empower women, which could accelerate the progress of child and maternal nutrition in India.